Empowering local MSMEs through digital sharia to foster the halal industry in South Kalimantan - Wahab, Abdul; Hadi, M. Qoshid Al; Rahman, Auliya; Mahdiya, Ilma (Community Empowerment, 2025)
This community service activity was designed to empower Micro, Small, and Medium Enterprises (MSMEs) using digital sharia principles to support the development of the halal industry in South Kalimantan. The primary target audience was the Indonesian Women Entrepreneurs Association (PERWIRA) of South Kalimantan Province. The program was delivered in a hybrid format, combining both in-person and online sessions to maximize reach and participation. The initiative resulted in a significant increase in the participants' digital sharia literacy. Participants began to adopt digital platforms that align with sharia principles in their business operations and showed a greater interest in the halal industry. Despite these successes, challenges were encountered, particularly related to the limited access to technology and inadequate digital infrastructure, which highlight the need for continuous support to ensure sustainable development. Overall, the activity successfully achieved its objectives and had a positive impact on the local halal industry. By enhancing digital sharia literacy and fostering greater participation among MSMEs, this program has the potential to drive sustainable economic growth in South Kalimantan.